Long-term evaluation of etiologic treatment with benznidazole in patients with indeterminate chronic Chagas disease - Hasslocher-Moreno, Alejandro Marcel (2012)
Fundação Oswaldo Cruz. Instituto Nacional de Infectologia Evandro Chagas. Rio de Janeiro, RJ, Brasil.